2019
DOI: 10.1016/j.euf.2018.04.014
|View full text |Cite
|
Sign up to set email alerts
|

A cost-effectiveness modeling study of robot-assisted (RARC) versus open radical cystectomy (ORC) for bladder cancer to inform future research

Abstract: Economic modeling showed that RARC might result in fewer complications, but is more expensive than ORC. Future research should focus on the impact on quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
1
16
0
1
Order By: Relevance
“…Considering the quality of the studies, the results indicated that, in general, RARC was more likely to be expensive. Michels et al conducted a cost simulation of ORC and RARC using data from a literature review and reported that RARC was more expensive [14], similar to our study result. Leow et al reported that the cost advantage in ORC was due to the additional costs of purchasing and maintaining robots and longer operative times for RARC [24, 28].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Considering the quality of the studies, the results indicated that, in general, RARC was more likely to be expensive. Michels et al conducted a cost simulation of ORC and RARC using data from a literature review and reported that RARC was more expensive [14], similar to our study result. Leow et al reported that the cost advantage in ORC was due to the additional costs of purchasing and maintaining robots and longer operative times for RARC [24, 28].…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, the cost-analysis by Bansal et al showed a total cost advantage of approximately $1945/case for ORC [13]. Michels et al [14] conducted a cost simulation of ORC and RARC and found that RARC costs €3365 more than ORC at 30 days. These studies indicated that operative time, length of stay (LOS), and the number of annual cases were key drivers of costs [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of an IDEAL 2b innovation already close to generalized adoption is robot-assisted radical cystectomy. 21,43 Robot-assisted surgery is maybe one of the most discussed innovations in surgery, because it has been adopted worldwide and demand for it is still rising, despite its high costs and lack of high-quality evidence. 65 IDEAL 3 innovations were mostly close to general adoption; an example is a trial-based cost-effectiveness analysis of mitral valve replacement for severe ischemic mitral regurgitation.…”
Section: Innovation Characteristicsmentioning
confidence: 99%
“…However, this is an expensive approach reserved for centers equipped with a robotic system. Thus, ORC remains the most widely performed approach worldwide with shorter operation times [17], equivalent oncological and perioperative outcomes at substantially reduced costs [18].…”
mentioning
confidence: 99%